2015
DOI: 10.1111/fima.12085
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity Benefits from IPO Underpricing: Ownership Dispersion or Information Effect

Abstract: The positive relation between initial underpricing and liquidity in the secondary market several months after the initial public offering has been previously attributed to ownership dispersion induced by underpricing. We show that public information production can be another channel by which underpricing improves liquidity. Using a sample of IPOs undertaken on Euronext, we show that the analyst coverage engendered by initial underpricing reduces information asymmetry costs and illiquidity in the secondary mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…Both Mantecon and Poon (2009) and Bouzouita et al. (2015) show that insider ownership influences post‐IPO liquidity. Second, we include Insider Sales i , which is a dummy variable that takes the value of one if the IPO company has insider selling in the weeks following the offering, and zero otherwise.…”
Section: Data Empirical Design and Methodsmentioning
confidence: 99%
“…Both Mantecon and Poon (2009) and Bouzouita et al. (2015) show that insider ownership influences post‐IPO liquidity. Second, we include Insider Sales i , which is a dummy variable that takes the value of one if the IPO company has insider selling in the weeks following the offering, and zero otherwise.…”
Section: Data Empirical Design and Methodsmentioning
confidence: 99%
“…Regarding fundamental analysis, [Bouzouita et al, 2015] suggested underpriced stocks in an IPO were more actively traded and carried lower liquidity costs. This underlined the importance of analysts' activity around IPOs not only for aftermarket prices, but also for the liquidity of the secondary market in the months following the IPO.…”
Section: Ipo Processmentioning
confidence: 99%
“…Earlier studies suggested information asymmetry as the main factor causing mispricing of IPOs by the offering firm. (see Bouzouita, Gajewski, & Gresse, 2015;McGuinness, 2016;Naifar, 2011;Wahid et al, 2020). An example of the asymmetry theory suggests that investors misprice the offering due to incomplete information relating to the firm's specific characteristics (Wahid, Khan, et al, 2019).…”
Section: Factors Affecting Ipo Pricingmentioning
confidence: 99%